Preliminary Numerical Investigations of Entropy Generation in Electric Machines Based on a Canonical Configuration - Toni Eger; Thomas Bol; Dominique Thévenin; Rüdiger Schroth; Gábor Janiga (Entropy, 2015)
The present paper analyzes numerically the entropy generation induced by forced convection in a canonical configuration. The configuration itself includes two well known fluid dynamic problems: (1) an external flow (flow around a cylinder, Kármán flow); and (2) an internal flow (flow between two concentric rotating cylinders, Couette flow). In many daily engineering issues (e.g., cooling of electric machines), a combination of these problems occurs and has to be investigated. Using the canonical configuration, the fields of entropy generation are analyzed in this work for a constant wall heat flux but varying two key parameters (Reynolds numbers Re∞ and Re0). The entropy generation due to conduction shows an absolute minimum around Re0 = 10,000. The same minima can be found by a detailed analysis of the temperature profile. Thus, entropy generation seems to be a suitable indicator for optimizing heat exchange processes and delivers a large amount of information concerning fluid and heat transport.